Literatur Review: Kemampuan Representasi Matematis Siswa dengan menggunakan Media Pembelajaran Matematika - Dika Dani Septiati (Prodi Pendidikan Matematika STKIP Persada Khatu;istiwa Sintang, 2022)
This article aims to describe students' mathematical representation abilities by utilizing mathematics learning media. Research using the literature review method is based on previous studies that are relevant regarding mathematical representation abilities, as well as a mathematics teaching media. From articles obtained by searches through Google Scholar and also the Science Direct and ERIC databases. The number of articles studied was 21 from national and international journals indexed by Sinta and Scopus. The results of the study show that using mathematics learning media can improve and train students in solving mathematical problems. One of the abilities students must have is the ability to represent mathematically, so that it is easier to present a solution to a problem. Keywords: Mathematical Representation Ability, Mathematics Learning Media.